Otimização de topologia aplicada ao projeto conceitual de edifícios usando o método da estrutura base - Silva, Sara Brandão e (2016)
Topology optimization provides design solutions to several engineering applications and density methods are the most popular approach in this field. However, when it comes to building design, the dimension of the extended domain related to the high of the building provides material concentration at the basis of the building. On the other side, the ground structure method provides desirable grid solutions using a highly connected truss in an approach close to size optimization techniques. This work presents a prospective study about the application of ground structure method to obtain bracing systems for buildings comparing with the known solutions obtained by density methods. Desirable manufacturing constraints such as patterns repetition and symmetry are considered. Multiple loading functions are Simulations are developed in two-dimensional building configurations to validate the method and show the structural comportment. Three dimensional examples are developed to show possibility of interesting solutions obtained with the ground structure method.